2017
DOI: 10.1016/j.jcomdis.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Signaling of noncomprehension in communication breakdowns in fragile X syndrome, Down syndrome, and autism spectrum disorder

Abstract: The ability to indicate a failure to understand a message is a critical pragmatic (social) language skill for managing communication breakdowns and supporting successful communicative exchanges. The current study examined the ability to signal noncomprehension across different types of confusing message conditions in children and adolescents with fragile X syndrome (FXS), Down syndrome (DS), autism spectrum disorder (ASD), and typical development (TD). Controlling for nonverbal mental age and receptive vocabul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 88 publications
2
32
1
Order By: Relevance
“…Differences in symptom expression have also been observed between FXS and nonsyndromic ASD, making it particularly important to define carefully those areas of overlap and divergence, in order to understand how FMR1 may contribute to ASD-relevant symptomatology. In this vein, and in line with prior work (see Abbeduto, McDuffie, & Thurman, 2014;Martin et al, 2017), this study employed a component-feature approach to further clarify specific pragmatic skills (i.e., communication repair) that may be differentially impacted in FXS and ASD, as well as DS. The limited studies on communication breakdown in FXS and DS have focused primarily on the ability to signal noncomprehension (confusion) when presented with unclear messages.…”
Section: Pragmatics and Communication Repair In Different Neurodevelomentioning
confidence: 90%
See 2 more Smart Citations
“…Differences in symptom expression have also been observed between FXS and nonsyndromic ASD, making it particularly important to define carefully those areas of overlap and divergence, in order to understand how FMR1 may contribute to ASD-relevant symptomatology. In this vein, and in line with prior work (see Abbeduto, McDuffie, & Thurman, 2014;Martin et al, 2017), this study employed a component-feature approach to further clarify specific pragmatic skills (i.e., communication repair) that may be differentially impacted in FXS and ASD, as well as DS. The limited studies on communication breakdown in FXS and DS have focused primarily on the ability to signal noncomprehension (confusion) when presented with unclear messages.…”
Section: Pragmatics and Communication Repair In Different Neurodevelomentioning
confidence: 90%
“…The limited studies on communication breakdown in FXS and DS have focused primarily on the ability to signal noncomprehension (confusion) when presented with unclear messages. For example, studies found that individuals with DS (Abbeduto et al, 2008;Martin et al, 2017) and FXS (Abbeduto et al, 2008;Thurman, Kover, Brown, Harvey, & Abbeduto, 2017) were less likely than TD controls to signal noncomprehension of a confusing message, with additional evidence that comorbid ASD negatively impacts this skill in FXS (Martin et al, 2017). No studies other than the study by Levy et al (2003), which included one male with FXS, have examined the ability of individuals with FXS to repair their own statements, and only one case study of four children has investigated repair skills in DS, with findings showing appropriate responses to requests for clarification (Coggins & Stoel-Gammon, 1982).…”
Section: Pragmatics and Communication Repair In Different Neurodevelomentioning
confidence: 99%
See 1 more Smart Citation
“…The existing literature has been mixed with regard to these latter domains. Although several studies have pointed to sex-differences in pragmatics, behavior, and communication skills (Lund, 1988 ; Berglund et al, 2001 ; Määttä et al, 2006 ; Van Gameren-Oosterom et al, 2011 ; de Sola et al, 2015 ; Lee et al, 2017 ), studies focused on the adolescent period specifically have generally shown no sex differences with regard to pragmatics (Martin et al, 2017 ) or behavior (Jacola et al, 2014 ). Taken together, these results suggest that sex differences in DS may vary as a function of chronological age and developmental level and, perhaps, the context of assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Future research may also consider alternative methods, such as lab‐based measures to confirm or further delineate patterns of phenotypic specificity between DS and FXS across certain areas. For example, within the Communication domain, children with DS may demonstrate greater needs in expressive skills whereas children with FXS may have greater needs in the area of pragmatic language abilities (Abbeduto, Warren, & Conners, ; Martin et al, ). Another limitation is the lack of assessment of ASD features in the DS group.…”
Section: Limitations and Future Researchmentioning
confidence: 99%